The mouse C-type transient receptor potential 2 (TRPC2) channel: Alternative splicing and calmodulin binding to its N terminus - Yildirim, Eda (The National Academy of Sciences, 2003)
Channels of the C-type transient receptor potential (TRPC) are involved in agonist-stimulated and capacitative calcium entry. There are seven TRPCs, all of which have a Ca(2+)-dependent calmodulin (CaM)-binding domain in their C termini. We now tested binding of CaM to TRPC N termini and show that only that of TRPC2 binds CaM in a Ca(2+)-dependent manner. Four TRPC2 cDNAs have been reported: a (also clone 14), b (also clone 17), α, and β. Sequences responsible for CaM binding in TRPC2 a and b are absent from the α and β isoforms. The α and β cDNAs of TRPC2 were reported as alternative forms, when recloning of TRPC2 a and b proved impossible. Here we analyzed total RNA samples from brain and testis for presence of TRPC2 a and b and describe the splicing patterns responsible for their formation, as well as those leading to the α and β forms of TRPC2. We re-assert existence of RNA encoding the TRPC2 a and b, encoded in 21 exons with an initiator ATG in exon 2 for TRPC2a and in exon 4 for TRCP2b. The analysis of α and β TRPC2 cDNAs indicates that although the TRPC2β mRNA may exist, the TRPC2α cDNA is derived from an incompletely processed TRPC2a mRNA: It includes in its presumed 5′-untranslated sequence, 713 nt of TRPC2a cDNA fused to 291 nt of an incompletely excised intron. While encoding an active channel in the mouse, the human TRPC2 appears to be a pseudogene. We searched for the human gene in the data bank and located approximately one-half of it in a chromosomal region syntenic to that of the mouse, with similar intron–exon structure. We conclude that the human TRPC2 gene may never have been an active gene because of incomplete ancestral duplication or, if it was complete at one point, that it became inactive upon loss of chromosomal sequences.